Thermodynamic Properties of Fe-Bearing Wadsleyite and Determination of the Olivine-Wadsleyite Phase Transition Boundary in (Mg,Fe)2SiO4 System - Su, Chang; Liu, Yonggang; Fan, Dawei; Song, Wei; Jiang, Jiyi; Sun, Zhenjun; Yang, Guang (Frontiers in Earth Science, 2022)
The self-consistent molar volume, elastic and thermodynamic properties of β-(Mg0.87,Fe0.13)2SiO4 wadsleyite have been determined over a wide temperature and pressure range based on an iterative numerical approach and experimental data from the literature. The obtained molar volume, adiabatic bulk modulus, and shear modulus generally agree with the available experimental and theoretical results, consequently proving the accuracy of our determined thermal expansion, heat capacity, and entropy. The thermodynamic properties of α-(Mg0.9,Fe0.1)2SiO4 were also reinvestigated. Comparisons on thermodynamic properties show that the thermal expansions, heat capacities, and entropies of both β-(Mg0.87,Fe0.13)2SiO4 and α-(Mg0.9,Fe0.1)2SiO4 exhibit negative and nonlinear behavior with increasing pressure. Besides, the pressure plays a more important role in thermodynamic properties of the α-(Mg0.9,Fe0.1)2SiO4 than that of the β-(Mg0.87,Fe0.13)2SiO4. Using the Clausius-Clapeyron equation combined with molar volumes and entropies of both compositions, the phase transition boundary of Fe-bearing olivine and wadsleyite is estimated. The calculated transition pressure shows a nonlinear relationship with increasing temperature, and the value is generally lower than the previous studies on Fe-free olivine and wadsleyite at the same temperature. On the basis of our phase relation, the temperature at the 410 km discontinuity is estimated as 1795±70 K under anhydrous conditions. The results not only confirm the feasibility of the Clausius-Clapeyron equation in obtaining the solid-solid phase transition, but also suggest that the existence of Fe might decrease the transition pressure of olivine-wadsleyite, which could consequently cause a higher temperature at the 410 km discontinuity.